PRESEPSI MASYARAKAT TERHADAP WISATA MANGROVE MUNDU PESISIR KABUPATEN CIREBON - Zulkifli, Ricki; Herlina, Nina; Nurdin, Nurdin (Journal of Forestry And Environment, 2024)
This study aims to determine the community's perception of the mangrove Mundu Pesisir tourism , Cirebon Regency. The information is expected to contribute and add insight in the development of science related to public perceptions of tourism, as well as provide an overview of public perceptions of the Mangrove Mundu Pesisir Tourism of Cirebon Regency. Data collection techniques were carried out by interview, observation,  and  literature  study,  the  method  of  determining  respondents  was  determined  by  purposive sampling, the number of respondents was taken as much as 98 people, analyzed of community perception data was carried out using a Likert Scale formula after getting the results of the questionnaire distributed to each respondent who had determined, and to obtain conclusions the data were analyzed descriptive qualitative.  The people of  Mundu Pesisir Village know that; a) Mangroves are part of the sea creatures ecosystem that must be preserved, b) Mangrove cultivation can help the economy, c) Develop awiq-awiq or village customary rules for mangrove management where if there is a violation of customary rules mangrove area management needs to be given sanctions or penalties , d) The community wants counseling from the government about the management of mangrove areas on a regular and sustainable basis. The people who were respondents refused to use the mangrove area as a settlement, because it would threaten their lives as well with fears that it could cause various disasters later. The people of Mundu Pesisir Village support the development of the Mundu   Pesisir mangrove area into natural tourism because the community wants natural tourism facilities and educational facilities for children who are close to their homes.